Do research papers provide enough information on design and material used in ankle foot orthoses for children with cerebral palsy? A systematic review. (August 2017) - Eddison, N.; Mulholland, M.; Chockalingam, N.
Objectives: The purpose of this article is to determine how many of the current peer-reviewed studies of ankle foot or-thoses (AFOs) on children with cerebral palsy (CP) have included adequate details of the design and material of the AFO, to enable the study to be reproduced and outcomes clearly understood. Methods: A thorough search of studies published in English was conducted in March 2015, with no restriction on dates, within all major databases using relevant phrases. These searches were then supplemented by tracking all key references from the appropriate articles identified. Study selection: The inclusion criteria were as follows: (1) population - children with CP; (2) intervention - AFOs; and (3) outcome measure. One reviewer extracted data regarding the characteristics of the included studies, with the extracted data checked for accuracy and completeness by a second reviewer. None of the studies reviewed gave adequate details of the AFOs. Only 3.6% (n = 2) of papers tested the stiffness. Many studies (54.5%) did not describe the material used nor the material thickness (72.7 %). None of them gave any clinical justification for the chosen design of AFO. Conclusions: There is a clear paucity of detail regarding the design and material used in AFOs on studies involving children with CP. Such a lack of detail has the potential to affect the validity of the reported outcomes, the ability to reproduce the studies and may misinform clinical practice.